Applied ethnobotany: People, wild plant use and conservation - Cunningham, Anthony B. (New York Earthscan, 2001)
Its wise and sensitive approach to working with local people will be relevant in situations throughout the world.' ECOS 'The numerous diagrams, tables of data, information flow charts, fieldwork sketches etc. give a great vibrancy to the work... It deserves a wide readership.' TEG News Wild or non-cultivated plants are crucial to the lives of a large portion of the world's population, providing low-cost building materials, fuel, food supplements, medicines, tools and sources of income. Despite their importance, their vulnerability to harvesting and other social impacts is not well understood.